Investigation on the Strengthening Mechanism of Flow Control Extrusion by Using Experiment and Numerical Simulation - Wu, Guangshan; Li, Yangqi; Chen, Fei (Materials, 2021)
Bimodal grain structure leads to high strength and strain hardening effect of metallic materials. In this study, an effective approach called flow control extrusion (FCE) is proposed to achieve heterostructures of pure copper. Compared with conventional extrusion (CE), FCE shows much stronger grain refine ability and much weaker grain orientation concentration. The significant grain refinement and heterostructures depend on the severe shear strain from FCE. The heterostructures of sample subject to FCE transfer from bimodal structure to gradient structure with the decrease of temperature, as the grains in the surface of sample are all refined to ultrafine scale. Both these two heterostructures can realize the improvement of strength and strain hardening effect simultaneously.